Clinical features of dog- and bat-acquired rabies in humans - Udow, S. J.; Marrie, R. A.; Jackson, A. C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Clinical differences in rabies due to canine and bat rabies virus variants have been noted, but no detailed studies have been reported to support these observations. Using PubMed and the MMWR we identified 120 case reports of rabies from the USA, Canada, Europe, and Asia. We systematically abstracted selected clinical features, results of investigations, incubation times and durations of illness. Details about clinical features were recorded. Cases were classified as dog- or bat-acquired based on reported animal exposure or viral variant typing by molecular or monoclonal antibody characterization. Categorical variables were summarized as frequency (%), and continuous variables were summarized as median (interquartile range [IQR]). We compared batand dog-acquired cases using chi-square or Fisher’s exact tests for categorical variables, and Mann Whitney U tests for continuous variables. Of 120 cases, 38 (32%) were dog-acquired and 54 (45%) were bat-acquired. Survivors and cases acquired from aerosolized viral exposure or tissue/organ transplantation were excluded. The median incubation times for dog- and bat-acquired rabies were 63 (IQR 42.75, 108) and 52.5 (IQR 27.25, 92.5) days, respectively (p=0.074). The median durations of illness for dog- and bat-acquired rabies were 17 (IQR 11.75, 23) and 14 (9.25,18.5) days, respectively (p=0.201). There was no difference in patients with bat- and dogacquired rabies in terms of the presence of fever, prodromal malaise, encephalopathy, sore throat, cranial nerve abnormalities, hemiparesis or seizures. Clinical manifestations that were more common in bat- than dog-acquired rabies included a local prodrome of sensory or motor symptoms (p=0.026), hemisensory abnormalities (p=0.042), tremor (p=0.003), and myoclonus (p=0.009). Neither tremor nor myoclonus was observed in patients with dog-acquired rabies. Aerophobia and facial or pharygneal spasms were more common in dog- than bat-acquired rabies (p=0.007 and p=0.029, respectively). Hydrophobia was more common in dog-acquired rabies (p=0.054). There was no difference between dog- and bat-acquired rabies in terms of results of diagnostic investigations such as skin biopsy, salivary analysis or the detection of antibodies in serum and cerebrospinal fluid (CSF). The CSF protein was higher for bat rabies (79; IQR 52, 109 mg/dL) than dog rabies (31; IQR 26, 48, mg/dL,; p=0.012). In summary, bat-acquired rabies is associated with more local symptoms, tremor, and myoclonus, whereas dog acquired rabies has more hydrophobia, aerophobia, and pharyngeal or facial spasms. We speculate that these clinical differences may reflect differences in the route of viral entry of the rabies virus variants into the nervous system because fundamental differences in the neuropathology or viral distribution have not been identified. Bat rabies virus variants may also have greater effects on the blood-CSF barrier by affecting endothelial cell permeability through unknown mechanisms.